Legal Issues of Ganti Tikar Marriage in Bugis Wajo Custom in East Tanjung Jabung Regency - Agusta, Acendra; Sajjad, Mohammad Ali; Azmi, Miftahudin (TRUNOJOYO LAW REVIEW, 2024)
Tanjung Jabung Regency, the author's research area, has various tribes: Bugis, Banjar, Batak, Java, and Padang. The Bugis tribe is further divided into Bugis Wajo, Bone and Pinrang tribes. Because their customs also have differences, the author only focuses on the Bugis Wajo tribe community because the Bugis Wajo tribe has traditions or customs that are still thick about marriage. The study focuses on the legal issues of ganti tikar marriage in Bugis Wajo customs in East Tanjung Jabung Regency. The research method used is empirical legal research with a socio-legal approach. The result of this study is that the marriage of ganti tikar by Bugis Wajo in East Tanjung Jabung Regency is permissible and valid as long as the terms and conditions of marriage are fulfilled. At the same time, in positive law, it is a traditional marriage that can be carried out as long as it does not conflict with applicable regulations.